Development of expertise in elite and sub-elite British rugby league players: A comparison of practice experiences - Rothwell, M.; Stone, L. A.; Davids, K.; Wright, C. (European Journal of Sport Science, 2017)
Previous studies have investigated how individuals reach an expert level by counting the number of hours engaged in specific practice types. Here we sought to understand and compare the microstructure (e.g. practice tasks undertaken) of these practice hours experienced by elite and sub-elite British rugby league players. Semi-structured interviews explored the practice experiences of eight international and eight domestic level players. A two-staged thematic analysis was used to interpret the data. The analysis revealed that both player groups experienced a rich and narrow landscape of affordances and were exposed to early diversification of sports experiences during childhood. Differences were identified in domestic level players` experiences of amateur and professional sports, where episodes of negative developmental environments were reported. International players` practice experiences revealed differences in their professional careers, where exposure to scenario-based practice and dynamic learning environments were reported. The findings suggest that insights from ecological dynamics provide a suitable theoretical framework to guide coaches in the design of practice environments that should consider the physical, psychological, emotional and social dimensions of expertise acquisition.